Sex differences in microRNA expression in first and third trimester human placenta. Issue 3 (7th December 2021) - Flowers, Amy E; Gonzalez, Tania L; Joshi, Nikhil V; Eisman, Laura E; Clark, Ekaterina L; Buttle, Rae A; Sauro, Erica; DiPentino, Rosemarie; Lin, Yayu; Wu, Di; Wang, Yizhou; Santiskulvong, Chintda; et al.
Abstract: Maternal and fetal pregnancy outcomes related to placental function vary based on fetal sex, which may be due to sexually dimorphic epigenetic regulation of RNA expression. We identified sexually dimorphic miRNA expression throughout gestation in human placentae. Next-generation sequencing identified miRNA expression profiles in first and third trimester uncomplicated pregnancies using tissue obtained at chorionic villous sampling ( n = 113) and parturition ( n = 47). Sequencing analysis identified 986 expressed mature miRNAs from female and male placentae at first and third trimester (baseMean>10). Of these, 11 sexually dimorphic (FDR < 0.05) miRNAs were identified in the first and 4 in the third trimester, all upregulated in females, including miR-361-5p, significant in both trimesters. Sex-specific analyses across gestation identified 677 differentially expressed (DE) miRNAs at FDR < 0.05 and baseMean>10, with 508 DE miRNAs in common between female-specific and male-specific analysis (269 upregulated in first trimester, 239 upregulated in third trimester). Of those, miR-4483 had the highest fold changes across gestation. There were 62.5% more female exclusive differences with fold change>2 across gestation than male exclusive (52 miRNAs vs 32 miRNAs), indicating miRNA expression across human gestation is sexually dimorphic. Pathway enrichment analysis identified significant pathways that were differentially regulated in first and third trimester as well as across gestation. This work provides the normative sex dimorphic miRNA atlas in first and third trimester, as well as the sex-independent and sex-specific placenta miRNA atlas across gestation, which may be used to identify biomarkers of placental function and direct functional studies investigating placental sex differences. Abstract : Sex dimorphism in miRNA expression is more pronounced in first compared to third trimester placenta, and there are 62.5% more female exclusive gestational differences, indicating miRNA abundance across human gestation is also sexually dimorphic.